Evaluation of the knowledge regarding vitamin D, and sunscreen use of female adolescents in Iran - Afsane Bahrami; Zahra Farjami; Gordon A. Ferns; Parichehr Hanachi; Majid Ghayour Mobarhan (BMC, 2021)
Abstract Background Vitamin D (Vit D) deficiency/insufficiency is an important risk factor for several chronic conditions. We aimed to evaluate the knowledge and behavior of female adolescents with respect to the association between sunlight exposure, sunscreen use, and Vit D status. Methods This cross-sectional survey was performed in northeastern Iran, among 940 female adolescents in January 2015. Each subject completed a questionnaire containing items about demographic characteristics, knowledge about Vit D and their use of sunscreen. Serum Vit D levels were measured using an electrochemiluminescence method and dietary intake of Vit D was assessed using a Food Frequency Questionnaire. Statistical analyses were conducted using SPSS software. A P value < 0.05 was considered statistically significant. Results Few of the participants were aware of the biological functions of Vit D (8.8%), the causes of Vit D deficiency (16.7%), and the sources of Vit D (9.3%). Less than half of the participants used sunscreen during the day. The serum levels of Vit D in subjects who used sunscreen were significantly lower than those who did not (p = 0.004). However, there was no significant association between their knowledge about Vit D and serum Vit D, or dietary intake of Vit D. Conclusion There appears to be a lack of coherence between lifestyle, behavior and knowledge that may affect the Vit D status of adolescent girls in northeastern Iran. This information provides a basis for developing public health planning (workshops or training at the college level) for the prevention of Vit D deficiency especially in adolescent girls.